Dinamika Keadilan dalam UU Cipta Kerja: Analisis Putusan Mk Dari Perspektif Pekerja dan Pengusaha - Yarni, Meri; Amir, Latifah; Prasna, Adeb Davega; Ramadhona, Ana; Dhyta, Nova Bela (Universitas Batanghari Jambi, 2025)
The notion of justice has long captivated the minds of philosophers, religious scholars, politicians, and legal experts alike. One of the challenges in this realm is that there is no absolute benchmark for determining fairness; what seems equitable to one party may not resonate with another. As a result, perceptions of fairness tend to be subjective, often leaving certain stakeholders dissatisfied. This complexity fuels ongoing debates within various cases that emerge in both national and state contexts. In this article, we explore the intricacies of these debates through the lens of the recent Constitutional Court Decision No. 91/PUU-XVIII/2020 concerning the Job Creation Law, which many view as favoring employers over workers. The Court's ruling deemed the law conditionally unconstitutional, igniting discussions about its implications for justice. To analyze the impact of this decision on both workers and employers, we apply the frameworks of procedural, substantive, and distributive justice theories. Our research employs a normative juridical approach, examining the Constitutional Court’s ruling alongside relevant laws and legal doctrines.